The geological controlling factors of the heterogeneity of a bioclastic limestone reservoir—a case study of the Cretaceous Kh2 layer in A oilfield, Iraq - Ling, Can; Zhang, Xiran; Fu, Meiyan; Huang, Tingting; Duan, Guanghui; Gao, Shumin (Frontiers in Energy Research, 2024)
Reservoir heterogeneity is one of the key factors affecting the exploration and development of oil and gas reservoirs. The Kh2 layer in this A field of Central Iraq is a major pay zone with strong longitudinal and lateral heterogeneity. The heterogeneity controlled by geological factors has not yet been confirmed, which seriously restricts the development of this pay zone. This study aims to establish a geological pattern for the reservoir heterogeneity of bioclastic limestone, providing a geological basis for heterogeneity evaluation. Based on the core observation, thin sections identification and physical property analysis, the microfacies are classified, and the diagenetic sequences and the pore structure of the Kh2 layer are analyzed. Seven types of microfacies are developed in the Kh2 layer, e.g. planktic foraminiferium wackestone (MFT1), lamellar bioclastic wackestone (MFT2), intraclastic-bioclastic packstone (MFT3), green algae packstone (MFT4), green algae-pelletoid packstone (MFT5), bioclastic-intraclastic packstone (MFT6) and intraclastic grainstone (MFT7). The heterogeneity of the different microfacies and heterogeneity within the same microfacies were evaluated using the variation coefficient of permeability tested from cores collected from wells and calculated by well-logging at different intervals. There is the highest heterogeneity in the lamellar bioclastic wackestone (MFT2), with the average variation coefficient of 0.72. There is the lowest heterogeneity in the green algae packstone (MFT4), with the average variation coefficient of 0.11. The vertical heterogeneity of the permeability is mainly controlled by sedimentation, while the lateral heterogeneity is mainly influenced by cementation, bioturbation and the distribution of green algae. Finally, a micro-scale geological pattern for reservoir heterogeneity of bioclastic limestone reservoirs is established. This study can guide the current injection development and remaining oil prediction in the oil fields with the similar background.